An Analysis of the Impact of Deviatoric Stress and Spherical Stress on the Stability of Surrounding Rocks in Roadway. (31st August 2021) - Rui, Liu; Quanjie, Zhu
Abstract : In this study, a detailed analysis was conducted to evaluate the impacts of the deviatoric stress component and spherical stress component on the stability of surrounding rocks in the roadway via the theoretical analysis and calculation and numerical simulation. Based on the analysis, the distribution laws guiding the main stress differences, plastic zone, convergence of surrounding rocks, and third invariant of stress under various conditions (such as equal spherical stress and unequal deviatoric stress and equal deviatoric stress and unequal spherical stress) were developed, providing an optimization scheme for roadway support misunderstanding under the conditions of high spherical stress field and high deviator stress field. The study further reveals that under the circumstance of the constant spherical stress, the greater the deviatoric stress, the plastic zone range of the surrounding rock of the roadway, the range of tensile deformation of the surrounding rock, the amount of convergence of the surrounding rock, the probability of separation of the roof and floor of the roadway, and the principal stress difference and the main stress, the greater the concentration range of the maximum stress difference is, and the maximum principal stress difference is mainly concentrated in the roof and floor rocks of the roadway, and the greater the deviatoric stress, the greater the probability that the roof and floor rocks of the roadway will be separated, and the maximum principal stress difference is mainly concentrated in the roof and floor rocks of the roadway, the greater the deviator stress, the greater the concentration range of the maximum value of the principal stress difference and the principal stress difference; when the deviator stress is constant, the range of the plastic zone and the maximum principal stress difference concentration range of the surrounding rock of the roadway decrease with the increase of the ball stress, and the principal stress difference, the amount of convergence of the surrounding rock, and the range of tensile deformation increase with the increase of the ball stress. The maximum principal stress difference is mainly concentrated in the roof and floor rocks of the roadway. The principal stress difference increases with the increase of the spherical stress, and the maximum concentration range of the principal stress difference decreases with the increase of the spherical stress. After the method proposed in this paper optimizes the actual roadway support on site, the surrounding rock deformation of the roadway is small and the control is relatively ideal, which basically meets the engineering needs.